Peran Strategis Komunikasi Internal dalam Meningkatkan Keterlibatan dan Kinerja Karyawan - Jadden Gill Imanuel Josua Pello; Polikarpus Sepryanto Ulybinu; Alif Nur Rohman; Agil Putra Alda Kumara (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Internal communication is one of the important elements in human resource management, playing a role in shaping organizational culture, increasing employee involvement, and supporting overall organizational performance. This article reviews five selected scientific journals that highlight the relationship between internal communication and organizational performance, focusing on employee engagement as an intermediate variable. From the analysis of the five journals, it was found that effective communication has a positive influence on employee loyalty, motivation, and productivity. These studies also highlight the importance of the role of digital technology, communicative leadership, and an open organizational culture in strengthening internal communication.